The Influence of House Environmental Conditions With The Event Of Acute Respiratory Infections Disease in Kalasan Puskesmas, Sleman Regency Yogyakarta - Novita Sekarwati; Subagiyono Subagiyono; Patria Asda (Universitas Veteran Bangun Nusantara, 2021)
Acute respiratory infection ( tract is the major cause of morbidity and mortalitas an infectious disease in the world .Almost four million people were killed in tract every year , 98 % his caused by respiratory infections bottom . Broad house temperature and moisture lighting not qualified health will affect health home residents , this is because the process of exchange the flow of air from the outside in the house do not smoothly , so bacteria disease-causing ispa who were in the house cannot be out. The goal is to know the conditioning environmental physical home ( temperature , moisture and lighting ) with the genesis tract in toddlers in the puskesmas kalasan sleman. Methods used in research this is the method quantitative with the approach case control study the relationship between environmental conditions a house with the incident trac. Sig significance ( 2-tailed ) paired test sample t-test 0,045 between the temperature of the house with the genesis ispa , sig significance ( 2-tailed ) paired test sample t-test 0,301 between lighting a house with ispa scene in toddlers at puskesmas kalasan . Sig significance ( 2-tailed ) paired test sample t-test 0,301 between lighting a house with ispa scene in toddlers at puskesmas kalasan. There an effect the temperature with the incident ispa and it the weight is irrelevant lighting and moisture a house with occurrences of a disease ispa .The community will further develop the clean and healthy living behavior in creating of a healthy house .